Muhammed el-Bekrinin el-Feydu'l-Kudsi fi Fadli Ayeti'l-Kürsi adlı eserin tahkik ve incelemesi - Şazeli, Muhammed Hayr (My University, 2023)
Bu tez, Muhammed b. el-Bekri'nin el-Feydu'l-Kudsi Fi Fadli Âyeti'l-Kürsi adlı eserinin tahkik ve incelenmesi hakkındadır. Muhammed el-Bekri tefsir, fıkıh, hadis, arapça ve tasavvuf ilimlerinde bir çok önemli eserin müellifidir. Bununla birlikte, Muhammed el-Bekri öğrencilerine vermiş olduğu dersleri daha çok tefsir ve tasavvuf üzerinedir. el-Feydu'l-Kudsi Fi Fadli Âyeti'l-Kürsi risalesi, Ayete'l-Kürsi'nin faziletleri hakkındaki hadisleri kapsamaktadır. Bu hadisleri inceleyerek sıhhat derecelerini öğrenmek mümkündür. Bu tez iki bölümden oluşur: ellif, müellifin dönemi ve el-Feydu'l-Kudsi Fi Fadli Âyeti'l-Kürsi adlı eseri hakkındadır. Tezimizde müellifin kişisel ve ilmi kişiliği hakkında detaylı bir araştırma yapılmıştır. Müellifin yaşadığı dönemdeki ilimler hakkında ayrıntılı araştırma yapılmıştır. Özellikle dönemin müfessirleri yazmış oldukları tefsir eserleri hakkında geniş bilgilere yer verilmiştir. Daha sonra tahkiki yapılan eser hakkında önemli bilgilere yer verilmiştir. Bu kapsamda hazırlanan tezde; eserin müellifine nisbeti, elimizdeki eserin doğruluğu, müellifin metodolojisi, eserin kaynakları ve eserin ilmi eleştirisi konuları yer almaktadır. İkinci bölüm ise eserin tahkik bölümüdür. Metin çağdaş kavramlarla okuyucunun anlayabileceği bir şekilde hazırlanmış ancak müellifin vermek istediği mesajların orijinalliğine dikkat edilmiştir. Ayrıca, eserde geçen hadislerin tahrici de yapılmıştır. Tezin metni modern imla kullarına göre yazılmıştır. Hareke gerektiren kelimelerin harekeleri yazılmış ve garip kelimelerin yerine çağdaş kavramlar kullanılmıştır. Tezin son bölümüne sonuç ve öneriler yazılmış, kaynakça ve fihrist ek yapılmıştır.

This thesis is a study and edit of the book (Al-Fayd al-Qudsi fi Fadl Ayat al-Kursi) by Imam alShaykh the Gnostic of Allah Muhammad ibn Abi alHasan alBakri. Shaykh Muhammad alBakri was not only specialized in exegesis, but was an imam in jurisprudence, hadith and Tasawwuf, yet most of his gatherings and lessons were in Tasawwuf and Qur'anic exegesis. This book is considered a collection of hadiths about the virtues of Ayat al-Kursi, that, through which it is possible to study these hadith and study their respective chains of transmission, plus to look at their totality in order to know the degree of their authenticity and the extent of their acceptance. This dissertation comes in two parts: The first part is a study of the author, his era and the book, in which I did a deep research on his personal biography and then also his academic biography. In my research on the era of the author I touched on the state of legal sciences in that era, and expanded further in clarifying the state of the science of exegesis and their authors plus which books that have been produced in this field. I followed that by talking about the book that is in the process of being edited. I examined its attribution to the author and the ferocity of the text that we have. I then examined the author’s methodology, his sources and the academic observations regarding it. As for the second section Which is the editing of the text . I worked on producing the text in a modern and clear manner for the readers, and according to the intention of its author, Allah willing. I referenced all the hadith with their rank from the relevant books as I also attributed all the narrations and statements to their respective authors and books. I have checked the text according to modern Arabic standards and added vowelation to difficult words appropriately with their explanation. I concluded my work with some conclusions i drew from the work and recommendations to future researchers. I have appended to the thesis indexes and a list of sources and references.
Keywords: Ayeti'l-kürsi; el-Feydu'l-kudsi Review of the Work Named al-Feydu'l-kudsi fi fadli âyati'l-kursi; Kuran; Muhammed el-Bekri, 1523-1585. el-Feydu'l-Kudsi fi Fadli Ayeti'l-Kürsi; Muhammed Elbekri; Tefsir